Indicators of political stability within growth theory and its impact on the growth of the industrial sector in Saudi Arabia (An Empirical Study for the period 1998-2022) - Saqr, Taibah AbdulHamid; Shesha, Lamia Saud (Journal of Economic, Administrative and Legal Sciences, 2025)
The importance of this study is evident in the current context in which the kingdom of Saudi Arabia seeks to achieve its Vision 2030, which aims to diversify the economy away from dependence on oil and promote the growth of non-oil sectors, including the industrial sector. In order to achieve the objective of this study in determining the impact of political stability on the growth of the industrial sector and determining the direction of the causal relationship between them in the Saudi Arabia for the period (1998-2022). The study used the distributed time delay subjective regression analysis (ARDL) methodology to estimate the relationship in the short and long term and the causality test (Granger), in order to verify the hypotheses of the study, which is a statistically significant positive effect of political stability on the growth of the industrial sector economy in the Saudi Arabia as well as the existence of a statistically significant causal relationship between them. The study has found a long-term equilibrium relationship that goes from the independent variables (political stability, government effectiveness, fixed capital formation, inflation, labor force participation rate, trade openness) to the dependent variable (industrial sector growth) through the result of testing the limits of joint integration. The study also showed that its first hypothesis was realized through the results of the ARDL assessment, which confirmed the existence of a statistically significant positive two-term effect of political stability on growth in the industrial sector, as its long-term morale parameter appeared as well as its short-term morale stability. The second hypothesis was also verified by the Granger causality test, which revealed a unidirectional causal relationship from political stability to growth in the industrial sector. The study recommended the need to enhance political stability by following economic diversification policies that would reduce the effects of global economic fluctuations, especially oil price fluctuations, and directing monetary policies towards maintaining stable and low inflation rates to achieve economic stability that enhances the investment climate in the industrial sector, which in turn achieves prosperity and developmental sustainability in the economy of Saudi Arabia.
Keywords: Political Stability; Industrial Sector; Co-integration; ARDL; Granger Causality Test